Improving the Screening Instrument of Bipolar Spectrum Disorders: Weighted Korean Version of the Mood Disorder Questionnaire - Hong, Narei (Clin Psychopharmacol Neurosci, 2018)
OBJECTIVE: It is not easy to diagnose bipolar disorders accurately in the clinical setting. Although Korean version of the Mood Disorder Questionnaire (K-MDQ) is easily administered, it still has weakness regarding case finding. In this study, we suggest a new weighted version of the K-MDQ to increase its screening power. METHODS: Ninety-five patients with bipolar disorders and 346 controls (patients with schizophrenia, patients with depressive disorders, patients with anxiety disorders, and subjects without any psychiatric disease) were enrolled in this study. The subjects received brief information on the K-MDQ, and then independently completed the questionnaire. RESULTS: Using odds ratios, we constructed a new weighted K-MDQ (W-K-MDQ). Item 1 (feel so good or hyper) was weighted 7 times and item 4 (less sleep) 3.5 times. Item 7 (easily distracted) and item 11 (more interested in sex) were excluded. Part 2 (simultaneity) and 3 (functional impairment) were also excluded as in the original K-MDQ. The sensitivity of the W-K-MDQ with a cutoff value of 10 was enhanced to 0.789. The area under the receiver operating characteristic curve was increased to 0.837. CONCLUSION: We suggested a new formula for K-MDQ using 11 of its items. The W-K-MDQ can be easily applied with good sensitivity to screen for bipolar disorders in clinical settings in Korea. Further evaluations with larger samples are needed to establish the usefulness of the W-K-MDQ.